Effects of various supplemental starch and protein levels on ruminal fermentation and liquid passage of beef steers fed tallgrass-prairie hay - Cochran, R.C.; Vanzant, E.S.; Olson, K. C.; Jones, Timothy J.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effect of supplements containing various proportions of degradable intake protein (DIP) and starch on ruminal digestion characteristics of forage-fed beef steers was evaluated. Fluid passage rates, ruminal ammonia (N H), 3 and total volatile fatty acid (VFA) concentrations increased as the amount of supplemental DIP increased. Starch infused at .3% of BW increased molar proportion s of propionate and butyrate and decreased acetate, compared to feeding DIP alone. However, proportions of branched-chain VFA increased with DIP at all levels of starch infusion. Total digestible organic matter intake (TDOMI) was increased with each addition of DIP; however, infusing starch within a DIP level decreased TDOMI. Providing supplemental DIP is more important for improving the use of low-quality, tallgrass-prairie hay than is ruminally available starch.
Keywords: Beef; Beef steers; Protein; Starch; Supplements; Ruminal fermentation